PENGARUH RASIO KEUANGAN TERHADAP RASIO PROFITABILITAS UNIT USAHA SYARIAH DI INDONESIA - Mochamad Indrajit Roy (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2018)
Abstract The process of transformation status of Commercial Banks that have a Sharia Business Unit (UUS) into a Sharia Commercial Bank (BUS) potentially be faster when viewed from the value of UUS ROA in the last three semesters which shows a value greater than BUS ROA. This study will analyze the effect of financial ratios to ROA on UUS. This research is quantitative research. The analysis used in this research is Multiple Regression. The analysis results in this study indicate that the variables of the financial ratios of NPF, NOM, and FDR simultaneously have a significant effect on ROA. Whereas if each variable was carried out, only NOM has a significant influence, while the rests do not.